Mathematical modelling for critical statistics education - Sampaio, Luana Oliveira [UNESP]; Wodewotzki, Maria Lucia Lorenzetti [UNESP] (Springer Nature, 2015)
This study involved 55 students of the discipline Statistics for Administration. With them, we conducted an extracurricular activity through Mathematical Modelling (MM) in an attempt to create conditions for a Critical Statistics Education (CSE). In this line, MM involves investigations of reality, while providing an environment where students gain space for discussions. Those discussions that have some connection with the construction of the Mathematical Model are what Barbosa (Students’ discussion in mathematical modelling, Istanbul, Turkey, 2006) calls Modelling Routes, which consists of three types of discussions: mathematical, technological, and reflexive. However, outside the Modelling Routes, there are the Parallel Discussions, that refers to general aspects of the problem without being used in the construction of the mathematical model. In our research, we identified new branches within the Parallel Discussions (Sampaio, Educação Estatística Crítica: uma possibilidade? Dissertação (Mestrado)—IGCE, Universidade Estadual Paulista, Rio Claro, Brasil, 2010): Mathematical Parallel Discussions: refers to the speeches belonging to the field of pure mathematics and/or statistics; Technological Parallel Discussions: refers to the way, or set of procedures and tools used to plan, develop, and evaluate the learning environment; Reflexive Parallel Discussions: refers to ideas related to aspects of social life and can involve socio-critical interpretations of the results of mathematical or statistical studies; Other Parallel Discussions: refers to the speeches that do not meet the definitions above. Faced with this classification, we observe that the discussions outside the Modelling Routes can also have an important role in MM Practices. We conclude that the Reflexive Discussions and Reflexive Parallel Discussions contribute more to the development of CSE, that, according to Campos (A educação estatística: uma investigação acerca dos aspectos relevantes à didática da estatística em cursos de graduação. Tese (Doutorado)—IGCE, Universidade Estadual Paulista, Rio Claro, Brasil, 2007), brings together the goals of Statistics Education and goals of Critical Education in order to produce a pedagogy that is democratic, reflective, and engaged in its greatest role of social responsibility with students.
Keywords: Critical statistics education; Discussions; Mathematical modelling